Effects of Chinese traditional ethnic sports on sleep quality among the elderly: a systematic review and meta-analysis - Jiahui Liu; Xiong-Wen Ke; Yi Lan; Diana Yuan; Weihao Zhang; Jian Sun (PeerJ, 2025)
Objective Sleep disorders affect approximately one-fifth of the global elderly population, with poor sleep quality among old adults linked to an increased risk of chronic conditions such as cardiovascular disease, diabetes, and hypertension. Chinese traditional ethnic sports have garnered significant attention for their potential to enhance sleep quality in older adults; however, the effectiveness of these interventions remains controversial. This meta-analysis sought to evaluate the impact of Chinese traditional sports on the quality of sleep among older adults. Methods A systematic search of databases, including Web of Science, Pubmed, Embase, Cochrane, China National Knowledge Infrastructure (CNKI), Wanfang, and China Science and Technology Journal Database (VIP), was conducted to identify randomized controlled trials (RCTs) examining the effects of Chinese traditional ethnic sports on sleep quality in older adults. Two independent researchers screened the literature, extracted relevant data, and conducted a quantitative meta-analysis using Stata17 software. Subgroup analyses were performed, including forest and funnel plot generation, heterogeneity analysis, sensitivity analysis, and publication bias assessment. Results A total of ten studies met the inclusion criteria. The meta-analysis revealed that older adults who participated in Chinese traditional ethnic sports showed significantly lower total PSQI score s relative to non-participants (Hedges’s g = −0.60, 95% CI [−0.89 to −0.31], P < 0.05). Egger’s test suggested no significant publication bias. Sensitivity analyses revealed that the age of participants, intervention mode, frequency, and duration did not substantially affect the combined effect size. Significant improvements were observed in sleep quality (Hedges’s g = −1.06, 95% CI [−2.00 to −0.13], P < 0.05), sleep duration (Hedges’s g = −0.52, 95% CI [−0.87 to −0.17], P < 0.05), and sleep efficiency (Hedges’s g = −0.50, 95% CI [−0.81 to −0.18], P < 0.05). Conclusion Chinese traditional ethnic sports are highly effective in improving the sleep quality of older individuals, demonstrating significant benefits in sleep quality, duration, and efficiency. Additionally, these interventions may reduce the reliance on sleep medications.